Caryospora bigenetica (Apicomplexa: Eimeriidae) in South America: new hosts and distribution records - Lúcio André Viana; Kamilla Costa Mecchi; Leonardo França do Nascimento; Heitor Miraglia Herrera; Paula Helena Santa-Rita; Marcos Tobias de Santana Miglionico; Rhaiza Gama Esteves; Anibal Rafael Melgarejo Gimenez; Fernando Paiva (Revista Brasileira de Parasitologia Veterinária)
The coccidian Caryospora bigenetica was first described in the snake Crotalus horridus (Viperidae) from United States of America. This study represents the first record of the occurrence of C. bigenetica in snakes in South America. Feces were sampled between November 2013 and May 2014 from 256 wild snakes maintained in scientific breeding facilities in the states of Mato Grosso do Sul (MS; n = 214) and Rio de Janeiro (RJ; n = 42), Brazil. Caryospora bigenetica was found in 14 (5.6%) snakes, all belonging to the family Viperidae. Ten Bothrops moojeni and two Crotalus durissus from MS were infected. The coccidian was also found in one C. durissus and in one Bothrops jararacussu from the state of RJ. The oocysts were spherical with a double wall, the exterior lightly mammillated, striations apparent in transverse view, 13.0 µm (12 – 14); polar granule fixed in the internal wall. Sporocysts oval or pyriform, 10.0 × 8.0 µm (9 – 11 × 8 – 9); Stieda body discoid; sub-Stieda body present; sporocyst residuum present, formed by a group of spheroid bodies between sporozoites. This study increases the number of viperid hosts of C. bigenetica and expands the geographical distribution to South America.